Visualisasi Seni Keramik Karya F. Widayanto - Yuda Nugraha Jamaludin (PANTUN, 2017)
The polemic on the ceramic is a form of the artists’ explorations as their personal expression media. Generally, ceramic tends to be part of an applied art. The anxiety is related to the view that ceramic is a usable thing. F Widayanto popularizes the ceramic art to the world of fne art exhibition. His artwork has distinctive characteristic on the tradition with detail curve and the coloring glaze which tends to be eye-fascinating. The visualization on his works is beyond the function rules tied to ceramic.This study is aimed at in-depth analysis on the visualization of F. Widayanto’s ceramic artworks. The method applied is qualitative by using Clive Bell aesthetic approach, in which started by datacollection and then analysis of F. Widayanto’s ceramic artworks. Basically, ceramic art is not merely about moving the word “ceramic” to the arts. Ceramic, although labelled as traditional arts, is proved to be existed among other contemporary artworksKeywords: F. Widayanto, ceramic art, visualization, aesthetic